Dentro de Alaska salvaje - Pascoe, Elaine; Pascoe, Elaine; Corwin, Jeff. (Detroit : Blackbirch Press, 2005)
Television personality Jeff Corwin takes the reader on an expedition through the harsh environment of Alaska, and introduces some of the diverse wildife found there.
Includes bibliographical references and index.
Keywords: Corwin, Jeff -- Travel -- Alaska -- Juvenile literature; Spanish language materials; Animals -- Alaska -- Juvenile literature; Alaska -- Description and travel -- Juvenile literature